Linguistic reflections of children’s transformation from Circadian to Newtonian time and the direction of time - OZCAN, Mehmet (International Journal of Scientific Research and Management (IJSRM), 2018)
Both linguistically and conceptually, the acquisition of time by children is pretty late when the process is compared with the acquisition and usage of linguistic elements denoting objects, states, actions and situations. This study investigated how children transform their Circadian time to Bergsonian time and how they encode Newtonian time linguistically.The study was carried out by the researcher’s longitudinal observation of his three daughters from the ages 2 to 10.  In order to verify the idiosyncratic temporal production of the three children, cross-sectional data were also collected using a day organization test.The results show that, (a) children between the ages of 3 and 4 live more in deictic time in that they refer to momentarily completed events such as a parent’s or sibling’s coming home or doing something which is worth mentioning from point of view of the child (“Baba geldi” ‘Daddy is home.’ or “düştü” ‘(it) fell’). (b) Children live in the Circadian time until the ages of 8-11 in that they conceive of and state time with reference to zeitgebers such as sleep-wake or day-night cycles. They also live simultaneously in Bergsonian time in that they refer to temporal units (e.g. days) with reference to the closest temporal unit (e.g. Dünden sonra” ‘The day dfter yesterday’ to mean the day before yesterday and “Yarından sonra” ‘The day after tomorrow’. (d) They begin to adopt Newtonian time with reference to certain successive events such as “Two days earlier” and then refine their conceptualization of Newtonian time by referring to hours (but not minutes).  (e) Children are pretty ahead of Newtonian time in the construction of complex temporal relations linguistically.